MIDDLE-LATE TRIASSIC RADIOLARIANS FROM THE DZHUGADZHAK SECTION (THE OMOLON MASSIF) - Bragin N.Yu.; Egorov A.Yu. (My University, 2000)
Radiolarians were found in the upper Anisian, upper Ladinian, and lower Carnian deposits of the Omolon massif. Their assemblages are less diverse than the coeval Mediterranean assemblages but very similar to the Middle Triassic assemblages of New Zealand. The identified cosmopolitan species of the assemblages enable correlation between Triassic deposits in the high and low latitudes.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая